Circadian system and aging: where both times interact - García Cobarro, Claudia; Ignez Soares, Lara; Kutsenko, Yevheniy; Tomas-Loba, Antonia (Frontiers in Aging, 2025)
Time shapes life both through its steady progression, as seen in aging, and through its eternal return, reflected in biological rhythms. These two temporal forces have sculpted organisms from their evolutionary beginnings, intertwining the processes of circadian regulation and senescence into the emerging concept of circadian aging. From the earliest prokaryotic lifeforms, the ability to sense and anticipate environmental cycles conferred evolutionary advantages, leading to the emergence of endogenous circadian clocks that regulate nearly every aspect of physiology. The mammalian circadian system is far more complex than a single master clock, comprising multiple tissue-specific oscillators entrained by diverse zeitgebers such as light, food, and activity. Importantly, circadian function deteriorates with age, contributing to hallmarks of aging including metabolic dysfunction, cognitive decline, immunosenescence, and disrupted sleep. Yet species with negligible senescence, such as naked mole-rats, tend to retain robust circadian rhythms throughout life, suggesting that temporal homeostasis may serve as both a marker and a modulator of healthy aging. This review explores the dynamic interplay between circadian time and chronological time, highlighting their shared regulatory pathways. We examine how circadian rhythms change naturally with age and in pathological conditions, the molecular crosstalk between clock genes and aging-related pathways and emerging evidence that circadian interventions can restore rhythmicity and promote healthspan. By unraveling the mechanisms of circadian aging, we aim to illuminate novel chrono-geroprotective strategies to enhance resilience and improve quality of life across the lifespan.